2019
DOI: 10.1002/hpja.229
|View full text |Cite
|
Sign up to set email alerts
|

Confident and Understanding Parents (CUPs) – a child nutrition and active play pilot intervention for disadvantaged families attending Supported Playgroups in Victoria, Australia

Abstract: Issue addressed Health and nutrition inequalities are prevalent among families from socio‐economically disadvantaged backgrounds. However, there is limited evidence of targeted early childhood nutrition and active play approaches due to the methodological challenges in engaging vulnerable families in research. Methods The aim of this paper was to report findings from a pilot intervention called Confident and Understanding Parents (CUPs). CUPs aims to improve child nutrition and active play‐related outcomes for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…This also applies to playgroups in the Netherlands, which offer structured and unstructured play experiences for children and provide opportunities for parents and their children to connect and socialize, but focus less on healthy behaviours. While this structure and the relaxed setting of playgroups provide a unique opportunity to support parents in their practices regarding health-related behaviours, there are limited interventions targeting such behaviour in these settings and most of them focus on promoting physical activity or nutrition [ 35 , 38 , 67 , 68 ]. A previous study among parents in Australia identified barriers to and facilitators of the development of a potential childhood obesity prevention programme, with a broader focus on lifestyle domains which could be delivered in community playgroups [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This also applies to playgroups in the Netherlands, which offer structured and unstructured play experiences for children and provide opportunities for parents and their children to connect and socialize, but focus less on healthy behaviours. While this structure and the relaxed setting of playgroups provide a unique opportunity to support parents in their practices regarding health-related behaviours, there are limited interventions targeting such behaviour in these settings and most of them focus on promoting physical activity or nutrition [ 35 , 38 , 67 , 68 ]. A previous study among parents in Australia identified barriers to and facilitators of the development of a potential childhood obesity prevention programme, with a broader focus on lifestyle domains which could be delivered in community playgroups [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nicola Wiseman, Christin Rossmann, Jessica Lee and Neil Harris explore the world of the pre‐school child through the innovative approach of drawing to determine their physical activity preferences. Judith Myers and colleagues report on the findings of a pilot intervention to improve nutrition and active play in young children (0‐4 years). Isaac Addo and co‐authors talk with sub‐Saharan African people to determine the influences on diet and physical activity post‐migration, while Jenny Olsen and colleagues investigate the physical activity behaviours of the peri‐urban populations through a socio‐ecological lens, and a whole of community physical activity and social engagement program shows promising outcomes …”
mentioning
confidence: 99%